(untitled) (Географический вестник=Geographical bulletin, 2017)
Дана характеристика основных техногенных источников загрязнения вод бассейна р. Камы в Пермском крае и приведены количественные показатели загрязнения рек железом и марганцем. TECHNOGENIC SOURCES OF INCOME OF IRON AND MANGANESE TO THE WATER OF THE KAMA RIVER BASIN The article provides description of the main industrial sources of pollution of The Kama River basin in Perm region and the quantitative indicators of water pollution with iron and manganese.